Associations Between Maternal Thyroid Function and Birth Outcomes in Chinese Mother-Child Dyads: A Retrospective Cohort Study - Chen, Geng-Dong; Pang, Ting-Ting; Lu, Xia-Fen; Li, Peng-Sheng; Zhou, Zi-Xing; Ye, Shao-Xin; Yang, Jie; Shen, Xiu-Yin; Lin, Dong-Xin; Fan, Da-Zhi; Lu, De-Mei; Liu, Zheng-Ping (Frontiers in Endocrinology, 2021)
Objective Although research suggests a close association between maternal thyroid function and birth outcomes, no clear conclusion has been reached. We aimed to explore this potential association in a retrospective cohort study. Methods This study included 8985 mother–child dyads. The maternal serum free tetraiodothyronine (FT4), thyroid-stimulating hormone (TSH), and thyroid peroxidase antibody (TPO Ab) concentrations and birth outcome data were reviewed from medical records. Subjects with TPO Ab concentrations of >34 and ≤34 IU/ml were classified into the TPO Ab positivity (+) and TPO Ab negativity (−) groups, respectively. Results Compared with subjects in the normal group (0.1 ≤ TSH < 2.5 mIU/L and TPO Ab−), those with TSH concentrations of 2.5–4.0 mIU/L and TPO Ab− had a 0.65-fold lower risk of low birth weight (LBW). In contrast, those with TSH concentrations of >4.0 mIU/L, regardless of the TPO Ab status, had a 2.01-fold increased risk of LBW. Subclinical hypothyroidism, regardless of the TPO Ab status, was associated with a 1.94-fold higher risk of LBW when compared with that in subjects with euthyroidism and TPO Ab−. No other significant associations were observed. Conclusion A maternal TSH concentration of 2.5–4.0 mIU/L was associated with a lower risk of LBW when combined with TPO Ab−, whereas subjects with a TSH concentration of >4.0 mIU/L had an increased risk of LBW. Subclinical hypothyroidism appears to be associated with a higher risk of LBW.